2021
DOI: 10.5812/ijpbs.108339
|View full text |Cite
|
Sign up to set email alerts
|

On the Causal Relationship Between Attachment Styles and Marital Satisfaction: Mediating Role of Gottman's Marital Communication Model

Abstract: Background: Marital satisfaction is one of the main factors affecting the quality of life in marital relationships. It refers to individuals’ positive attitudes toward their marital relationship, and marital dissatisfaction is a negative and displeased attitude toward various aspects of marital relationship. Objectives: The present study aimed to explore the causal relationship between attachment styles and marital satisfaction regarding the mediating role of Gottman’s marital communication model. Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In fact, it appears as if the whole system of education revolves around the Academic Achievement of students, though various other outcomes are also expected from the system. Gargari et al (2011) found the relationship between attribution and academic procrastination in University Students. The subjects were 203 undergraduate students, 55 males and 148 females, selected from English and French language and literature students of Tabriz University.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, it appears as if the whole system of education revolves around the Academic Achievement of students, though various other outcomes are also expected from the system. Gargari et al (2011) found the relationship between attribution and academic procrastination in University Students. The subjects were 203 undergraduate students, 55 males and 148 females, selected from English and French language and literature students of Tabriz University.…”
Section: Introductionmentioning
confidence: 94%
“…Sirois (2007) expressed that procrastination is a widespread problem related to self-regulation, which is realized as deferral of the beginning and completing the important, necessary assignments and it may produce important negative consequences such as anxiety and depression, regarding the personality. Garari & Sabiuri (2011) defined the Procrastination as a avoid or escape from undesirable tasks. The Procrastination usually justifies his action by saying that "This is a boring assignment; or will it later".…”
Section: Introductionmentioning
confidence: 99%
“…Research has established some precedence for suspecting that adult attachment styles could contribute to beliefs and experiences related to marriage. For example, recent findings have indicated significant associations between attachment styles and marital satisfaction (Azizi & Beyranvand, 2018; Mardani et al, 2021; Sebastian, 2018), marital intimacy (Aqaei & Mousavi, 2020; Bakhtiari et al, 2019), marital conflict (Cheraghisifabad et al, 2021; Fallah et al, 2019), marital adjustment (do Rosário Ramos Nunes Bacalhau et al, 2020; Sivandian & Besharat, 2019), and marital distress (Davarinejad et al, 2017; Elyasi et al, 2021). Furthermore, some research has identified links between attachment and marital attitudes and beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most important factors that has been focused on in recent years and affects marital intimacy is an individual's early experiences or the nature of their emotional relationship with their parents during childhood (Mardani et al, 2021). Khojasteh Mehr et al (2014) stated that women with an ambivalent attachment style not only create grounds for conflict and dispute with their spouse but also lack problem-solving skills to resolve issues and prevent ongoing conflicts (Khojaste Mehr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%